Application of natural rubber latex foam as an effective oil absorbent - Abdulhakim Masa; Nureeyah Jehsoh; Nabil Hayeemasae (Polímeros)
Abstract Oil spills have had catastrophic effects on marine ecosystems. The removal of oil spills from the water surface has then attracted worldwide attention. Natural rubber (NR) is a well-known example of a hydrophobic material, due to its hydrocarbon structure. For this purpose, the potential of NR as an oil absorbent is demonstrated. NR was formed into a cellular structure where oil absorbency can be controlled by their densities. It can be done by varying the foaming volume from 2-8 fold (2×, 4×, 6×, and 8×) the original volume of the beater. Increasing the foaming volume has reduced the densities. Over the variations of densities, the oil absorbencies were 10.58 to 16.76 g/g for crude oil, and 6.56 to 13.18 g/g for diesel oil. This indicated that the absorbent based on NR latex foam provided excellent performance and could be practically used as an oil-absorbent material.